2021
DOI: 10.3390/pathogens10081002
|View full text |Cite
|
Sign up to set email alerts
|

Canine Circovirus in Foxes from Northern Italy: Where Did It All Begin?

Abstract: Canine circovirus (CanineCV) is a recently identified virus affecting both domestic and wild carnivores, including foxes, sometimes in presence of severe clinical signs. Its circulation in wild animals can thus represent a potential threat for endangered species conservation and an infection source for dogs. Nevertheless, no data were available on its circulation in the Alps region of Northern Italy. In the present study, samples collected from 186 foxes in the period 2009–2020 from Valle d’Aosta and Veneto re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 43 publications
(61 reference statements)
3
14
0
Order By: Relevance
“…Similarly, another member of porcine circoviruses, Porcine circovirus 3, has been occasionally detected in ruminants, rodents, canines and insects [18]. Similar conclusions can be drawn for other circoviruses such as Beak and Feather Disease virus [20,21] or canine circovirus [22].…”
Section: Introductionsupporting
confidence: 65%
“…Similarly, another member of porcine circoviruses, Porcine circovirus 3, has been occasionally detected in ruminants, rodents, canines and insects [18]. Similar conclusions can be drawn for other circoviruses such as Beak and Feather Disease virus [20,21] or canine circovirus [22].…”
Section: Introductionsupporting
confidence: 65%
“…In our study, no wild carnivores i.e., foxes and wolves were sampled, thus preventing the evaluation of the epidemiological role of these animals in Iran. To date, circulation of CaCV in wild carnivores has been described only in European countries [ 12 , 13 , 14 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequent studies in China [ 4 ], Thailand [ 5 ], Turkey [ 6 ], Italy [ 7 ], Germany [ 2 ], Brazil [ 8 ], Argentina [ 9 ], Vietnam [ 10 ] and Colombia [ 11 ] have revealed that CaCV is broadly circulating in domestic dog populations worldwide. Interestingly, CaCV and genetically related CVs have also been detected in other canids, including wolves and foxes [ 12 , 13 , 14 , 15 , 16 ]. Moreover, recent evidence shows the virus might have circulated in wild species for a long time before its first discovery in 2012 [ 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, CanineCV was identified in Italy and was thought to be the causative agent of canine necrotizing vasculitis and lymph node granuloma, which can cause vomiting and hemorrhagic diarrhea in dogs [ 2 , 3 ]. To date, CanineCV has been reported in several countries, indicating that the virus has spread worldwide [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ]. The genome of CanineCV is approximately 2063–2064 nt in size and primarily contains three open reading frames (ORFs).…”
Section: Introductionmentioning
confidence: 99%